sage: solve(exp(-x)+exp(x) == 2,x) [x == 0] sage: solve(exp(-2x)+exp(2x) == 2,x) 
Can tell me anyone why the second equation has no solution?
I unfortunately don't have time to check why this doesn't work, but the following keyword argument (useful to know in any case) does work:
which should be interpreted as saying
for all possible solutions to the original one. Unfortunately, finding the documentation for this (currently) requires using the method notation instead of functional
posted Oct 02 '10kcrisman
6784 ● 14 ● 67 ● 152
Asked: Oct 02 '10
Seen: 241 times
Last updated: Oct 02 '10
powered by ASKBOT version 0.7.22
Copyright Sage, 2010. Some rights reserved under creative commons license.